Earnings Quality and ESG Performance in Energy and Utilities: What Really Matters? - Persakis, Antonios; Fassas, Athanasios P.; Philippas, Dionisis (International journal of finance and economics, 2025)
The paper investigates the controversial relationship between firms' earnings quality and environmental, social and governance (ESG) performance, focusing on the energy and utility sectors given their significant regulatory pressures, environmental impact, and capital‐intensive nature, which render ESG performance particularly important for financial reporting practices. Using a cross‐country dataset of firms in these sectors, we empirically assess whether ESG performance amplifies or dampens earnings quality, extending our framework to incorporate CEO power and board strength, with respect to a comprehensive set of firm‐specific and country‐level controls. We show that a higher level of ESG commitment is positively associated with improved earnings quality, suggesting that ethical engagement and transparency enhance the integrity of financial reporting. We find that CEO power weakens the positive relationship between ESG commitment and earnings quality, as managerial discretion may facilitate earnings management practices that obscure the firm's underlying financial condition. In contrast, strong boards amplify earnings quality by enhancing effective oversight and promoting corporate accountability. Nevertheless, board effectiveness is subject to the inherent trade‐offs between maintaining legitimacy, addressing diverse stakeholder interests, and meeting economic needs. We conclude that ESG initiatives are substantially shaped by internal corporate governance structure and firm‐specific operational characteristics.